Pengaruh Implementasi Kurikulum, Kompetensi Widyaiswara, Pengelolaan Sarana dan Prasarana terhadap Hasil Belajar Peserta Pendidikan dan Pelatihan Kemetrologian: Effect of Curriculum Implementation, Widyaiswara Competence, Facilities and Infrastructure Management on Learning Outcomes of Metrological Education and Training Participants - Budi Yasri; Heru Sujiarto; Ibrahim Danuwikarsa; Adjat Sudrajat (Society, 2022)
Implementing the curriculum, widyaiswara, and facilities are the main pillars in realizing the training process for metrological training participants in achieving the expected learning outcomes. Although the facilities can be considered adequate, the variables affecting improving the quality of learning outcomes of the metrology training participants need to be determined. The purpose of this study was to review the effect of curriculum implementation, widyaiswara, and facilities on the quality of learning outcomes for metrology training participants. This research method used a survey method with a quantitative approach. Data analysis was performed using linear regression test and T-test. The study’s results stated that the T-test on the variables of curriculum implementation, widyaiswara, and facilities, as well as their combination on learning outcomes, resulted in a significance value of less than 0.05 at the 95% confidence level. This study concluded that implementing curriculum, widyaiswara competencies, facilities, and a combination of the three positively and significantly impact the quality of metrological training participants’ learning outcomes.